XPANDED ROLE MANAGEMENT – CLOUD BUILDING CONSTRUCTION MANAGEMENT SYSTEM - ADUM .K; JIAWN YEN; ZINUAN MIANG, ADUM .K; JIAWN YEN; ZINUAN MIANG (International Journal of Multidisciplinary Research and Studies, 2021)
In terms of the construction industry, needs of construction management will differ based on different companies, personnel, projects and time. It is very difficult to meet different construction management needs in the industry with only one system. This study aims at developing a secondary development system that allows different users to design specific and customized construction management systems according to different needs. This study is not for the provision of solutions to single “management issues” but for the development of platforms applicable to various “management types’. Consequently, management efficiency and efficacy of relevant enterprises in the industry can be raised and the overall competitiveness of the industry can be enhanced. System automatic planning, construction, feedback, content adjustment, acceptance test, and procedure confirmation took in total 11 months. To make sure that the problem is helpful for labor dispatch and implementation effectiveness, training courses for competent authorities, special groups and enterprises, open sharing sessions and other qualitative interviews on experience were carried out to obtain feedback of users and thereby adjust platform development. In addition, 360 system users received a questionnaire investigation using a technology acceptance model. Judging from 107 valid questionnaires, the average score of perceived usefulness was 4.38 and that of perceived ease of use was 4.26. In terms of the average of the dimension, there was no significant difference in the background of the different respondents, indicating that most respondents were positive for the secondary development platform regarding construction management assistance and easy operation. Besides, dimensional relationships among perceived usefulness, perceived ease of use, attitude toward using and usage intention all indicate positive influence. During use of the system, feedback will be obtained through the online service platform to made adjustment and continuously offer system services, to achieve the study objectives set.